Gravity - Deming, Sarah (New York : Make Me a World, 2019)
Sixteen-year-old Gravity Delgado has been breaking records and competitors since she started boxing with a legendary coach at age twelve, and now will reach the Olympics if her home life and romance do not distract her.
Junior Library Guild
Ages 14-17.
Grades 9-12.
850
A Junior Library Guild selection
Keywords: Boxing -- Juvenile fiction; Conduct of life -- Juvenile fiction; Determination (Personality trait) -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Olympic athletes -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Boxing -- Fiction; Conduct of life -- Fiction; Determination (Personality trait) -- Fiction; Family problems -- Fiction; Olympic athletes -- Fiction; Racially mixed people -- Fiction; Boxing -- Fiction; Conduct of life -- Fiction; Family life -- Fiction; Olympic athletes -- Fiction; Racially mixed people -- Fiction